PENGARUH TRANSFORMATIONAL LEADERSHIP, KNOWLEDGE SHARING, DAN WORK ENGAGEMENT TERHADAP INNOVATIVE WORK BEHAVIOR PADA KARYAWAN JASA MARGA GROUP - Sarah Sofia; Daesy Aseanty (Modus, 2024)
This study aims to analyze the role of transformational leadership, knowledge sharing, and work engagement on innovative work behavior in Jasa Marga Group Employees. The data in this study were collected from a sample of 320 (three hundred and twenty) employee respondents from the head office and branch offices. This type of research is quantitative research with cross-sectional data collection techniques, as well as purposive sampling techniques and data collection is done by distributing questionnaires and literature studies. The method model used in this research is simple regression analysis using SPSS version 27. The results showed that transformational leadership, knowledge sharing, and work engagement have a positive influence on innovative work behavior. The results of this study are expected to provide input for company management to motivate employees to increase the role of transformational leadership, knowledge sharing and work engagement in increasing the role of innovative work behavior and provide support in the form of appreciation for employees who have initiated innovation and provide loyalty for the benefit of achieving company goals. Keywords: transformational leadership; knowledge sharing; work engagement; innovative work behavior. Penelitian ini bertujuan untuk menganalisis peran Transformational Leadership, Knowledge Sharing, dan Work Engagement terhadap Innovative Work Behavior pada karyawan Jasa Marga Grup. Data pada penelitian ini dikumpulkan dari sampel berjumlah 320 (tiga ratus dua puluh) responden karyawan dari kantor pusat dan kantor cabang. Jenis penelitian ini adalah penelitian kuantitatif dengan teknik pengambilan data secara cross-sectional, serta teknik pengambilan sampel secara purposive sampling dan pengumpulan data dilakukan dengan melakukan penyebaraan kuesioner dan studi pustaka. Model metode yang digunakan dalam penelitian ini adalah analisis regresi sederhana dengan menggunakan SPSS versi 27. Hasil penelitian menunjukan bahwa transformational leadership, knowledge sharing dan work engagement memiliki pengaruh positif terhadap innovative work behavior. Hasil penelitian ini diharapkan dapat memberikan masukan bagi manajemen perusahaan untuk memotivasi karyawan dalam meningkatkan peran transformational leadership, knowledge sharing dan work engagement dalam meningkatkan peran innovative work behavior, serta memberikan dukungan berupa apresiasi terhadap karyawan yang telah menggagaskan inovasi, dan memberikan loyalitasnya untuk kepentingan dalam mencapai tujuan perusahaan. Kata kunci : transformational leadership; knowledge sharing; work engagement; innovative work behavior.